The Role of Islamic Commercial Laws in Addressing Unethical Practices in Northern Nigerian Markets - Usman Mukhtar (Al-Fadilah: Islamic Economics Journal, 2026)
This study investigated the role of Islamic Commercial Laws (ICL) in addressing unethical practices in Northern Nigerian markets, with the main objective of assessing the extent to which ICL principles can promote ethical business conduct and reduce fraudulent activities such as price manipulation, usury, and the sale of substandard goods. The research was carried out in selected markets across Kano, Gumel, Hadejia, Daura, and Katsina, which are notable commercial hubs within Northern Nigeria. The subjects of the study included market traders, consumers, Islamic scholars, and representatives of Islamic financial institutions. A total sample of 100 participants was used for the quantitative aspect, while 10 individuals were selected for in-depth interviews. The sample was selected through a combination of purposive and stratified random sampling to ensure representation across stakeholder groups. The study was guided by structured research questions aimed at identifying the prevalence of unethical practices, the level of awareness of ICL among market participants, and the challenges of enforcement. Data were collected using a combination of structured questionnaires, semi-structured interviews, direct market observations, and document reviews. Quantitative data were analyzed using descriptive statistics such as frequency counts, percentages, and mean scores, while qualitative data were thematically analyzed and interpreted in line with the research objectives. The findings revealed widespread unethical behaviors in the markets, including inflated pricing, exploitation in informal credit systems, and a general lack of transparency. Challenges identified included lack of education, weak enforcement structures, and limited access to Islamic financial institutions. Based on these findings, the study recommended extensive public sensitization on ICL principles, integration of ICL into market regulation frameworks, expansion of Islamic microfinance services, and collaboration between religious authorities, market leaders, and government agencies to promote ethical trade. The study concludes that while ICL provides a robust ethical framework, its practical impact depends on education, institutional support, and active enforcement.